Intergenerational Transfer of Persistent Bacterial Communities in Female Nile Tilapia - Abdelhafiz, Yousri; Fernandes, Jorge M. O.; Donati, Claudio; Pindo, Massimo; Kiron, Viswanath (Frontiers in Microbiology, 2022)
Resident microbial communities that can support various host functions play a key role in their development and health. In aquatic animals, microbial symbionts are vertically transferred from the parent fishes to their progeny. Such transfer of microbes in mouthbrooder fish species have not been reported yet. Here, we employed Nile tilapia (Oreochromis niloticus) to investigate the vertical transmission of microbes across generations using a 16S rRNA amplicon sequencing approach; based on the presence of bacteria in different generations. Our analysis revealed that the core microbiome in the buccal cavity and posterior intestine microbiome shapes the gut microbiome of progenies across generations. We speculate that the route of this transmission is via the buccal cavity. The identified core microbiome bacteria, namely Nocardioides, Propionibacterium and Sphingomonas were reported to play an essential role in the health and development of offspring. These core microbiome members could have specific functions in fish as described in the case of mammals.